Development of Manning'N for selected high gradient rivers in Malaysia / Hannah Priscilla Egon - Egon, Hannah Priscilla (Faculty of Civil Engineering, 2007)
Although there have been much research done on Manning’s roughness coefficient, n in the United State of America for the stream channels. There have been no such attempts done for the high Gradient River in Malaysia. The n value is determined from the values of factors that affect the roughness of channels. The n value for high Gradient River can be determine by measuring the geometrical properties and the particle sizes of the soil in the river. There are a few field sampling that involve in the research. Which are determining cross section, slope, velocity, and bed material. Through the data taken from the river, it is analyse using the sieve analysis. From the sieve analysis, we can get the d84 which will be used as parameter in determining the n value. The equation used is the Limerinos (1970). In this research, there are also verifications for the applicability and reliability of the Manning’s roughness coefficient.